Effect of Ambient Temperature and Light Intensity on Growth Performance and Carcass Characteristics of Heavy Broiler Chickens at 56 Days of Age - Olanrewaju, H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2010)
The effects of ambient temperature, light intensity and their interaction on growth performance and carcass characteristics of broilers were investigated in 2 trials. The experiment was consisted of a factorial arrangement of treatments in a randomized complete block design. The 9 treatments consisted of 3 levels (Low = 15.6, Moderate = 21.1, High = 26.7oC) of temperatures from d 21-56 d of age and 3 levels (0.5, 3.0, 20 lx) of light intensities from 8-56 d of age at 50% RH. Five hundred and forty Ross 708 chicks were randomly distributed into 9 environmentally controlled chambers (30 males and 30 females chicks/chamber) at 1 d of age. Feed and water were provided ad libitum. Birds were provided a four phase-feeding program (starter: 1 to 14 d, grower: 15-28 d, finisher: 29-42 d and withdrawal: 43-56 d). At 56 d of age, both feed intake and birds’ weight were recorded for the growth performance. Also, 20 (10 males and 10 females) birds from each chamber were processed to determine weights and yields. Broilers subjected to high ambient temperature of 26.7oC had significantly (P